2010
DOI: 10.1186/1471-2180-10-31
|View full text |Cite
|
Sign up to set email alerts
|

Global transcriptomic response of Leptospira interrogans serovar Copenhageni upon exposure to serum

Abstract: BackgroundLeptospirosis is a zoonosis of worldwide distribution caused by infection with pathogenic serovars of Leptospira spp. The most common species, L. interrogans, can survive in the environment for lengthy periods of time in between infection of mammalian hosts. Transmission of pathogenic Leptospira to humans mostly occurs through abraded skin or mucosal surfaces after direct or indirect contact with infected animals or contaminated soil or water. The spirochete then spreads hematogenously, resulting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
64
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 89 publications
6
64
1
2
Order By: Relevance
“…Expression of the gene encoding LA0572, predicted to be involved in transport of ferrienterobactin (55), and expression of the gene encoding LA2242, a desferrioxamine receptor homolog, were upregulated (Table 2), similar to what was found in L. biflexa (44). Expression of la2242 is also induced by transition from low to physiological osmolarity conditions (48) and exposure to serum (57).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Expression of the gene encoding LA0572, predicted to be involved in transport of ferrienterobactin (55), and expression of the gene encoding LA2242, a desferrioxamine receptor homolog, were upregulated (Table 2), similar to what was found in L. biflexa (44). Expression of la2242 is also induced by transition from low to physiological osmolarity conditions (48) and exposure to serum (57).…”
Section: Resultssupporting
confidence: 57%
“…Since heme is likely to be the main source of iron in the host, upregulation of these genes was not surprising, especially given that heme oxygenase is required by L. interrogans for survival in the hamster model of infection (52). Genes encoding LB186 and LB187 were also upregulated in response to an increase in osmolarity (48) and exposure to serum (57), consistent with the importance of these genes for survival in the host.…”
Section: Resultsmentioning
confidence: 52%
“…We confirmed that clpB is upregulated during heat stress. ClpB was also found to be downregulated in response to serum (29) and under iron-depleted conditions (11).…”
Section: Discussionmentioning
confidence: 92%
“…Quantitation of transcript levels of selected genes. Many Leptospira genetic studies normalize to the endogenous flaB for gene expression analyses because it encodes a highly abundant protein that is synthesized under a variety of conditions (11,(37)(38)(39)(40). However, Leptospira spp.…”
Section: Resultsmentioning
confidence: 99%